Discourse on Skeptical Orientalist Methodology in the Study of Qur'anic Codification - Faldiansyah, Iqrom; Rif’ah, A. Muh. Azka Fazaka; Rizaldi, Muh. (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
The skeptical Orientalist discourse regarding the historical issue of the codification of the Qur'an, which is often stereotyped as being antagonistic towards the Qur'an, exhibits a heterogeneity of methodological approaches. The emergence of diverse methodologies among skeptical Orientalists is influenced by various underlying factors, leading to different implications as well. This study aims to examine the various methodologies proposed by skeptical Orientalists concerning the history of the canonization of the Qur'an. The diversity of methodologies, driven by differing interests, illustrates that the study of the codification of the Qur'an arises from scientific objectives rather than solely from an antagonistic stance towards the Qur'an. To substantiate this argument, the study employs qualitative methods, using primary data from the works of John Wansbrough, John Burton, and Alphonse Mingana, which are then analyzed using the pre-understanding theory developed by Hans Georg Gadamer. The study demonstrates that the diverse pre-understandings possessed by skeptical Orientalist figures, which subsequently give rise to specific objectives in studying the historical issues of the codification of the Qur'an, contribute to the heterogeneity of methods utilized in their studies. For instance, John Wansbrough employs modern Gospel studies—which have proven capable of liberating Gospel studies from fundamentalist tendencies—as a methodological basis in the study of Islam in general and the study of the Qur'an in particular, bringing it into the same skepticism developed in modern Gospel studies. This has implications for the importance of positioning the process of writing the Qur'an as a human process that can be tested, selected, proven, and objectively verified.